Natural Flora Improves Properties of Acid Soil in Rubber Plantations - and A. Ulaganathan, M.D. Jessy*, V.K. Syamala (Journal of the Indian Society of Soil Science, 2021)
Repeated monoculture of rubber (Hevea brasiliensis) for more than a century in traditional rubber growing regions has affected some of the soil properties and soil acidity is a major fertility constraint of plantations. There is also widespread concern about the biodiversity in monoculture plantations of Western Ghats, where spices and plantation crops dominate agriculture. Effect of natural vegetation, Pueraria phaseoloides and Mucuna bracteata, the common leguminous ground covers established in rubber plantations on pH, organic carbon and cation concentration in soil was studied. Soil samples were collected before and four years after establishing ground covers. Results revealed that Pueraria phaseoloides did not change soil pH, whereas Mucuna bracteata lowered and natural flora increased soil pH significantly. Soil organic carbon, calcium and potassium contents significantly improved under natural flora. Study clearly showed the advantages of natural vegetation to check soil acidification and to improve soil properties in tropical rubber plantations.